Boosting low-temperature CO2 methanation through Ni/ZrO2 catalyst-NaA zeolite interplay - Inam Ullah; Syed Musab Ahmed; Hao Lou; Zeeshan Abbasi; Zubair Ahmad; Muhammad Usman; Wenlong Wu; Zhandong Wang (Journal of Environmental Chemical Engineering, 2026)

Engineering metal organic framework 808 and MXene Interfaces for sustainable oxygen evolution electrocatalysis in alkaline media - Shumaila Bibi; Syed Shoaib Ahmad Shah; Muhammad Irfan; Faiza Jan Iftikhar; Mohamed H. Helal; Muhammad Zahid Qureshi; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

Toward sustainable mining: Experiment-based comparative investigation of energy absorption techniques for reducing air overpressure and enhancing rock fragmentation - Talib Hussain; Yasir Ahmad; Shahbaz Abbas; Afshan Naseem; Syed Tasweer Hussain Shah; Muhammad Zaka Emad (Engineering Geology, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Reversible -NH2/-NH3+ switching drives proton-coupled electron transfer for selective CO2-to-CO photoreduction in S-scheme MOF/g-C3N4 heterojunction - Sharafat Ali; Sher Ali; Ahmed Ismail; Yong Wang; Syed Ul Hasnain Bakhtiar; Qaisar Alam; Pir Muhammad Ismail; Wajid Ali; Ahmad Iqbal; Polycarpos Falaras; Jiabao Yi; Fazal Raziq; et al. (Chemical Engineering Journal, 2026)

Building Information Modelling (BIM) adoption in developing economies: an analysis of barriers, critical success factors, and a public infrastructure viability framework - Qaim Shah; Syed Saad; Muhammad Hasnain; Waseem Khan; Ijaz Ahmad; Abdul Haq (Innovative Infrastructure Solutions, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

Rebalancing α-Synuclein Clearance: Novel Therapeutic Frontiers in Parkinson’s Disease - Maryam Jabeen; Huma Hameed; Syed Muhammad Ahmad; Tehreem Mushtaq; Mahtab Ahmad Khan; Anam Hameed (NeuroMolecular Medicine, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Baseline Assessment of Municipal Wastewater Parameters in 20 Rural Areas of Punjab, Pakistan: A First-Ever Framework for Development of Sustainable Decentralized Treatment Plants - Abdul Manan; Tausif Ahmad; Syed Nadir Hussain; Hafiz Muhammad Anwaar Asghar (Water, Air, & Soil Pollution, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Morphology and phylogeny reveal a New Species and Two New Combinations of Xerocomellus (Boletaceae) from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Syed Mohammad Tauseeq Ali Shah; Dege Zheng; Umer Rehman; Atika Noor; Muhammad Asif; Dong-Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (Current Microbiology, 2026)

Biomedical applications of fungal-derived nanoparticles: bridging mycology and nanotechnology for next-generation therapeutics - Umer Rehman; Mohsin Ullah; Syed Mohammad Tauseeq Ali Shah; Muhammad Adnan; Ishtiaq Ahmad; Zabta Khan Shinwari (Plant Biosystems, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Valorization of rubber waste for the synthesis of an acidic heterogeneous catalyst for efficient palm fatty acid distillate esterification - Muhammad Aliyu; Junaid Ahmad; Chawalit Ngamcharussrivichai; Kamil Kayode Katibi; Syed Ahmar Ali Hashmi; Umer Rashid (Process Safety and Environmental Protection, 2026)

From climatic moderation to persistent hotspots: decadal insights into soil erosion risk from RUSLE–GIS modeling in the northwestern mountains of Pakistan - Khurrum Ahmad Khan; Syed Amer Mahmood; Muhammad Haseeb (CATENA, 2026)

Phylogeny and diversity study in Damani sheep through mitochondrial DNA D-loop nucleotides sequence - Muhammad Zohaib; Farhad Ali; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tariq Zeb; Ihsan Ali; Mohammad Qasim; Khalid Khan; Iftikhar Ahmad; Ijaz Ahmad (Tropical Animal Health and Production, 2026)

Artificial intelligence enabled fouling prediction and effect of adsorbent sources in submerged fluidized bed ceramic membrane reactor for food industry wastewater treatment - Tuba Safdar; Muhammad Iqbal; Aisha Syed; Maqbool Khan; Arshad Hussain; Jeonghwan Kim; Rizwan Ahmad (Environmental Research, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Disaster management technology and approaches: a focus on heterogeneous systems - Muhammad Haris; Sajjad Keshtkar; Adeel Anjum; Madiha Haider Syed; Hirohisa Kojima; Rafiq Ahmad (Environment Systems and Decisions, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Spatiotemporal analysis of climatic and anthropogenic drivers of winter smog in the Indo-Gangetic Plain with a focus on Lahore - Muhammad Zeeshan Ghani; Mujtaba Hassan; Farrukh A. Chishtie; Syeda Saleha Fatim Ali; Syed Waqar Hussain Shah; Ahmad Bilal (Environmental Science and Pollution Research, 2026)

A comprehensive review on thermo-responsive targeted and functional therapy for management of rheumatoid arthritis - Huma Hameed; Syed Sharf ud Din; Muhammad Zaman; Muhammad Ahsan Waqar; Kainat Fatima; Abdullah Ashraf; Huzaifa Malik; Ahmad Salawi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Experimental study on optimizing explosive energy distribution for a cost-effective solution to minimize blasting hazard and improve rock fragmentation - Talib Hussain; Yasir Ahmad; Shahbaz Abbas; Syed Tasweer Hussain Shah; Afshan Naseem; Muhammad Zaka Emad (Bulletin of Engineering Geology and the Environment, 2026)

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Integrated computational, pharmacological and molecular investigations of piperitone in mitigating Alzheimer disease pathology by targeting cholinesterases, β-secretase and neuroinflammation - Rubia Anwer; Ihsan Ullah; Arif-ullah Khan; Mushtaq Ahmad Mir; Nasreena Bashir; Syed Uzair Ali Shah; Muhammad Ayaz (Inflammopharmacology, 2026)

Improving Wheat Production in Pakistan Through an Economically Viable Solar‐Powered Rain Gun Sprinkler Irrigation System - Muhammad Asif; Shahzad Hussain Dahri; Bashir Ahmad; Noman Latif Sadozai; Sohail Raza Haidree; Abdul Hannan; Syed Qasim Ali Naqvi (Irrigation and Drainage, 2026)
In rainfed agriculture, limited water availability has become a challenging factor for sustainable farming and economic security. For regions with variable climate conditions, efficient water management practices must be adopted to improve livelihoods and food security. This study aimed to evaluate the role of supplemental irrigation for wheat crops in the Pothwar region. The irrigation management consists of I 0 (rainfed), I 1 (10 mm presowing), I 2 (10 mm at 50% soil moisture depletion [SMD]) and I 3 (25 mm at 75% SMD). The results revealed that, under I 3 , the grain yield increased by 49% and 17%, followed by I 2 (47% and 12%) compared to the rainfed yield of 1.85 and 3.93 tons/ha in Jand and NARC, respectively. The analysis of variance and Tukey's honestly significant difference (HSD) test revealed that the yield for I 0 value was significantly lower than that of all the irrigation treatments, while there were no significant differences among I 1 , I 2 and I 3 . The net benefit analysis revealed that I 3 was an economic irrigation schedule and paid back the total intervention cost by generating PKR 389,915/ha at NARC and PKR 283,915/ha at Jand in 3.83 and 4.93 years, respectively. This viable economic return makes solar‐powered irrigation systems reliable sources of water for water‐scarce and climate‐variable regions.

Mechanical power for ventilation - looking beyond the lung - Mutaz I. Othman; Majd M. AlBarakat; Ahmed S. Mohamed; Syed Muhammad Hassan; Rebecca R. George; Ahmad A. Omari; Emad M. Mustafa; Ali Ait Hssain; Hana J. Abukhadijah; Abdulqadir J. Nashwan (Next Research, 2026)

A comparative analysis of tsunami flow through emergent and submerged coastal vegetation using numerical simulation - Syed Muhammad Ahmad Bukhari; Naveed Anjum; Saad Abbas; Adnan Shahid; Abdul Basit Bukhari; Ghufran Ahmed Pasha (Natural Hazards, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Isolation and molecular characterization of plant growth-promoting rhizobacteria for biocontrol of Fusarium head blight in wheat - Syed Jehangir Shah; Somaira Bibi; Safira Attacha; Syed Tanveer Shah; Noreen Asim; Waqas Ahmad; Muhammad Sayyar Khan; Ishrat Naz; Muhammad Ibrahim; Aftab Jamal (Cereal Research Communications, 2026)

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

Calocybe barangensis sp. nov (Lyophyllaceae), from Bajaur, Pakistan - Mohsin Ullah; Malka Saba; Dege Zheng; Umer Rehman; Muhammad Asif; Syed Mohammad Tauseeq Ali Shah; Dong‐Qin Dai; Ishtiaq Ahmad; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this study, we report a new taxon, Calocybe barangensis , from Barang, Bajaur District, Khyber Pakhtunkhwa, Pakistan. The species was described as new to science using molecular phylogenetic analysis of combined ITS and LSU datasets, as well as comparisons of its macro‐ and micromorphological characteristics with those of similar taxa. The new species forms a separate clade in the phylogenetic tree and differs in having small basidiomata with dark yellowish‐brown spores and large, globose to subglobose basidiospores (5.9–7.2 × 4.7–5.6 μm). A full description, illustrations, and phylogenetic analysis results of the new species are provided.

YOLO-based real-time floating debris counting in urban rivers for flood monitoring and water resource management - Shaufikah Shukri; Latifah Munirah Kamarudin; Azfar Haniff Zuel Azwar; Noraini Azmi; Ammar Zakaria; Ahmad Shakaff Ali Yeon; Syed Muhammad Mamduh Syed Zakaria; Retnam Visvanathan (Environmental Monitoring and Assessment, 2026)
Urban flooding is increasingly exacerbated by the accumulation of floating debris in rivers, which obstructs water flow, degrades water quality, and poses significant risks to human safety and environmental sustainability. Effective monitoring of floating debris is therefore critical for early flood warning and long-term water resource management. This study presents a real-time monitoring framework that integrates deep learning-based object detection models, You Only Look Once (YOLO) with video surveillance for the identification and quantification of floating debris in urban rivers. Field deployments were conducted in flood-prone sites in Shah Alam, Malaysia, to evaluate the system under real-world environmental conditions. Results show that YOLOv7 achieved higher accuracy and robustness across diverse debris classes and lighting conditions compared to YOLOv9, with precision, recall, and F1-scores demonstrating strong detection reliability. Beyond technical accuracy, the system provides timely and actionable information for flood risk assessment, river management, and environmental monitoring. By automating debris detection and quantification, this study contributes to Sustainable Development Goals (SDGs) 11 (Sustainable Cities and Communities) and 13 (Climate Action), offering a scalable monitoring solution for flood-prone regions.

Greenhouse gas emission modeling for gulf cooperation council countries with boosting techniques - Muhammad Muhitur Rahman; Md Shafiul Alam; Bijoy Mitra; Mohammad Shahedur Rahman; Aftab Ahmad Khan; Muhammad Tahir Amin; Abdulmoez Al Ismaeel; Syed Masiur Rahman (Environment, Development and Sustainability, 2026)

MOF/Graphene interfaces in catalytic water splitting: Recent breakthroughs and future outlook - Asad Ur Rehman; Muhammad Asghar; Abdul Rauf; Tayyaba Najam; Ibrahim A. Shaaban; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Fuel, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Geographic distribution patterns, population dynamics, and habitat vulnerability of endangered and endemic Trillium govanianum - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Raja Waqar Ahmed Khan; Amir Sohail (Environmental Monitoring and Assessment, 2026)

Ecological Insights into Plant Diversity and Distribution Along Environmental Gradients in Haveli Kahuta, Pakistan - Syed Tahir Hussain Bukhari; Khawaja Shafique Ahmad; Muhammad Tayyib Riaz; Majid Mahmood Tahir; Ansar Mehmood; Ummar Iqbal; Tajmal Imtiaz; Hazem M. Kalaji; Manzer H. Siddiqui (Environmental Monitoring and Assessment, 2026)

Carbon-based materials for photocatalytic degradation of pharmaceuticals and drugs - Shan Arif; Sufian Rasheed; Naseer Ahmad; Muhammad Ikram Nabeel; Waqas Ahmad; Thamer Alomayri; Dilshad Hussain; Syed Ghulam Musharraf (Journal of Water Process Engineering, 2026)

Real-time terrain classification for all-wheel drive robotic electric tractors using multi-sensor fusion and machine learning - Tamiru Tesfaye Gemechu; Jun Zhou; Guoliang Lai; Ibrar Ahmad; Luke Toroitch Rottok; Yade Li; Tabinda Naz Syed; Muhammad Aurangzaib (Journal of Terramechanics, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Synergistic Ni single-atom–nanoparticle interfaces for poison-resistant CO₂ electroreduction - Syed Shoaib Ahmad Shah; Jamal Kazmi; Muhammad Altaf Nazir; Manzar Sohail; Muhammad Sufyan Javed; Tayyaba Najam; Lishan Peng; Ramón A. Alvarez-Puebla (Chemical Engineering Journal, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Recent progress of metallic nanomaterials in energy, biomedical and environment sector - Kinza Maqsood; Sami Ullah; Asad ur Rehman; Hafsa Bashir; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Next Research, 2025)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Engineering multifunctional fire proof superhydrophobic cotton fabric via sequential coating of flower-like PPPA/BMOF and PDMS - Tooba Ali; Naseer Ahmad; Waqas Ahmad; Hua-Ming Xiao; Syed Muhammad Jawad; Muhammad Imran Malik; Dilshad Hussain (Chemical Engineering Journal, 2025)

Sacrificial agent-free H2O2 production driven by S-scheme photocatalysis over hierarchical ZnO/UiO-66-NH2 heterojunction - Muhammad Adnan Qaiser; Jinhe Li; Wei Ren; Shahid Khan; Syed Bilal Ahmed; Waqar Ahmad Qureshi; Mohamed Hussein Abdurahman; Weikang Wang; Qinqin Liu (Chemical Engineering Journal, 2025)

The weight reducing effects of naltrexone-bupropion among obese psychiatric and non-psychiatric patients: a systematic review - Hafsah Alim Ur Rahman; Muhammad Ahmed Ali Fahim; Unaiza Naeem; Syed Hassan Ahmed; Muhammad Youshay Jawad; Hareem Arshad; Anil Kalyoncu; Mujeeb U. Shad; Ahmad Hameed (Psychopharmacology, 2025)

Variations in Wheat and Soil N Concentration by the Sole and Combined Foliar Application of NPK and Humic Acid Levels - Khadim Dawar; Shahid Ali; Ibad Ullah; Ishaq Ahmad Mian; Bushra Khan; Muhammad Tariq; Aamir Khan; Syed Sartaj Alam; Muhammad Mudasar Malik (Journal of Soil Science and Plant Nutrition, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

Taxonomic significance of pollen micromorphology in family Malvaceae from subtropical ecosystems - Prem Kumar; Mushtaq Ahmad; Syed Waseem Gillani; Muhammad Manzoor; Shazia Sultana; Lixin Zhang; Sokhib Islamov; Jamil Raza (Genetic Resources and Crop Evolution, 2025)

Nutlet micromorphology and systematic implications of genus Nepeta (Lamiaceae): correct taxonomic tool for taxa identifications - Shaista Jabeen; Mushtaq Ahmad; Muhammad Zafar; Shabir Ahmad; Hussain Shah; Ateef Ullah; Syed Waseem Gillani; Muhammad Manzoor; Ashraf M. M. Abdelbacki; Ali M. Sayed (Genetic Resources and Crop Evolution, 2025)

Morpho-palynological evaluation of family Poaceae from arid and semi-arid regions of Pakistan - Bibi Sadia; Mushtaq Ahmad; Wajia Noor; Syed Waseem Gillani; Muhammad Manzoor; Zhiduan Chen; Lixin Zhang; Shazia Sultana; Amir Sohail (Genetic Resources and Crop Evolution, 2025)

Circular Economy in Oilfield Systems: A Review of Culinary Waste Materials for Sustainable Drilling Fluids - Muhammad Hammad Rasool; Syahrir Ridha; Maqsood Ahmad; Numair Ahmed Siddiqui; Muhammad Khurram Zahoor; Azam Khan; Syed Abdul Moiz Hashmi (Circular Economy and Sustainability, 2025)

Exploring the relationships of trade globalization and financial inclusion with energy intensity in emerging economies: The role of technological innovation - Syed Anees Haider Zaidi; Shabbir Ahmad; Muhammad Wasif Zafar; Zokir Mamadiyarov (Journal of Environmental Management, 2025)

Environmental Concern and Digital Engagement as Drivers of Circular Product Buying Intention in Malaysia: an Integrated S-O-R, TPB, and DOI Perspective - Husam Ahmad Kokash; Mst. Nilufar Ahsan; Muhammad Haroon Hafeez; Amira Naqeeb Khattak; Saif Ahmed; Syed Shah Alam (Circular Economy and Sustainability, 2025)

Potential of Organic Amendments as a Sustainable Strategy to Enhance Rice Yield by Improving Nutrient Use Efficiency and Physiological Performance in Alkaline Soil - Muhammad Ahmed; Muhammad Tauseef Jaffar; Zulfiqar Ahmad; Muhammad Naveed; Syed Ayyaz Javed; Muhammad Shoaib Asad; Ali Raza; Awais Shakoor; Jianguo Zhang (Journal of Plant Growth Regulation, 2025)

An effective bi-functional electrocatalyst for electrochemical water splitting using NiCo2O4 nanoparticles decorated with Polypyrrole nanocomposite - Khadija-Tul-Kubra; Faiqa Noreen; Ali Junaid; Atif Nazir; Sehrish Arshad; Komal Bibi; Ayesha Batool; Aleeza Sattar; Aboud Ahmed Awadh Bahajjaj; Sohail Ahmad; Muhammad Shuaib Khand; Syed Imran Abbas Shah (Fuel, 2025)

Mechanistic insights into lead uptake and immobilization mediated by soybean biochar and arbuscular mycorrhizal fungi in Bidens parviflora - Sadam Khan; Irfan Ullah Shah Syed; Muhammad Riaz; Muhammad Tariq; Tahir shah; Sidra Sohail; Muhammad Imtiaz; Shoaib Akhtar; Jiang Yuanren; Munib Ahmad; Yurong Yang; Hanzhong Jia (Applied Soil Ecology, 2025)

Recent advances in layered double hydroixdes@MXene (LDHs@MXene) composites: Synthesis, properties, and catalytic applications - Sundas Riaz; Sami Ullah; Sanam Bashir; Aziz ur Rehman; Rashid Iqbal; Tayyaba Najam; Mostafa A. Ismail; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Applied Clay Science, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Transcriptional variation of meat quality marker genes in different age and sex groups of Balkhi breed sheep - Muhammad Farooq Akhtar; Rajwali Khan; Syed Muhammad Suhail; Abdur Rehman; Ijaz Ahmad; Iftikhar Ahmad; Farhan Anwar Khan; Faraz Ahmad; Athar Rehman; Muhammad Ayaz; Khalid Khan; Amel Ayari-Akkari (Tropical Animal Health and Production, 2025)

Phosphorus Modified Biochar and Vermicompost Integration Alleviated Cd Phytotoxicity in Wheat (Triticum aestivum L.) by Improving Growth, Antioxidant Activities and Reducing Cd Uptake in Plants - Ahmad Ali; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Waseem; Muhammad Rizwan; Muhammad Ali; Sobia Afzal; Syed Farhan Haider Bukhari; Usama Ali Tahir (Journal of Soil Science and Plant Nutrition, 2025)

Unlocking the Geoheritage Potential of Hingol National Park (HNP), Pakistan: Geological and Geomorphological Insights Through Multi-Satellite Remote Sensing Data and Field Geology Validation - Muhammad Yaseen; Rujun Chen; Jawad Ahmad; Shahid Ali Shah; Shah Fahad; Muhammad Naveed Anjum; Syed Tanvir Shah (Geoheritage, 2025)

Isolation, biochemical characterization, and antimicrobial activities of EPS-producing bacterial endophytes from Moringa oleifera - Karim Gul; Raham Sher Khan; Aneela Iqbal; Atta Ullah; Syed Muhammad Shafi Shah; Anwar Hussain; Douglas Law; Ayaz Ahmad; Salimullah Khan (Folia Microbiologica, 2025)

Sustainable water management practice in South Asian Countries: The importance of water resources, temperature, and bioenergy on ecological footprint - Muhammad Haroon Shah; Syed Tauseef Hassan; Irfan Ullah; Yaoyao Wang; Ashfaq Ahmad Shah (Gondwana Research, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Towards sustainable methanol production: energy, exergy, economics, and environmental evaluation of Thar coal gasification - Syeda Asra Arshad; Umna Nasir Ali; Syed Ali Ammar Taqvi; Bilal Kazmi; Ahsan Khalid; Muhammad Ahmer; Farooq Ahmad; Naveed Ahmad (Environment, Development and Sustainability, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Correction: Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

The role of corroles in modern cancer therapy: innovation and prospects - Laiba Javaid; Huma Hameed; Mahtab Ahmad Khan; Syed Muhammad Ahmad; Inaba Shujaat Qureshi; Rabia Shahzad; Ali Irfan (BioMetals, 2025)

Challenges and outlooks for the polyoxometalates, metal-organic frameworks (POMs-MOFs) hybrid materials in water treatment technologies - Ghulam Murtaza; Muhammad Ibrar Ahmed; Kewei Yu; Xingda An; Syed Shoaib Ahmad Shah; Manzar Sohail (Environmental Research, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Unveiling the Microplastics Menace in Freshwater Fishes: Evidence from the Panjnad Barrage, South Punjab, Pakistan - Syed Muhammad Moeen Uddin Raheel; Adnan Ahmad Qazi; Muhammad Latif; Huma Naz; Yasir Waqas; Maximilian Lackner (Fishes, 2025)
This study explored the prevalence and types of microplastic (MP) pollution in three fish species—Labeo rohita, Wallago attu, and Cirrhinus mrigala—collected from the Panjnad Barrage in South Punjab, Pakistan. MPs were analyzed from the gastrointestinal tracts (GITs), gills, and muscles of 90 fish samples. Advanced analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy/Energy-Dispersive X-Ray Spectroscopy (SEM/EDX), and Gas Chromatography/Mass Spectrometry (GC/MS), were deployed, confirming the polymeric composition and presence of various additives. Quantitative and qualitative analyses revealed significant variations in MP accumulation across tissues, with the GIT consistently showing the highest MP count, the gills having the highest concentration per gram, and the muscles exhibiting the lowest amount of accumulation. Wallago attu was found to have accumulated the highest concentration of microparticles among all three species due to its feeding habits and habitat. Fibers and fragments were the predominant types of MPs, with yellow and red being the most frequent colors. Polypropylene (PP) and polyethylene (PE) were the primary polymers identified, alongside other types like polyethylene terephthalate (PET) and polyvinyl chloride (PVC). The MP size distribution indicated that mid-sized particles (150–50 µm) were most abundant in the GIT and gills, while smaller particles (

Recovery and treatment of cooling tower blowdown water: Challenges, recent advancement, and future perspectives - Syed Taufiq Ahmad; Ashfaq Ahmad; Rizwan Ahmad; Ahmed Fuwad; Azeem Mushtaq; Muhammad Kashif Shahid (Journal of Environmental Chemical Engineering, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Exploring the taxonomic relevance: foliar epidermal microanatomy of aromatic and medicinal plants within subfamily Nepetoideae - Shaista Jabeen; Muhammad Zafar; Mushtaq Ahmad; Saeedah Musaed Almutairi; Mohamed Soliman Elshikh; Trobjon Makhkamov; Sokhib Islamov; Syed Waseem Gillani; Muhammad Manzoor (Genetic Resources and Crop Evolution, 2025)

Nano-revolution in aquaculture: quantum dot innovations for sustainable fisheries - Ulfat Batool; Syed Makhdoom Hussain; Shafaqat Ali; Azhar Rasul; Muhammad Mudassar Shahzad; Adan Naeem; Nisar Ahmad; Muhammad Munir; Abdul Ghafoor; Mohammad Ali Alshehri (Aquaculture International, 2025)

Exploring multimetal interactions between FeNi3 alloy and Lu3Ga5O12 metal oxide for improved water splitting performance - Muhammad Ammar Hassan Shah; Zahoor Ahmad; Karam Jabbour; Khadija Bibi; Zubaida Fareed; Syed Imran Abbas Shah; Alanoud T. Alfagham; Abdallah M. Elgorban; Faryal Aftab; Muhammad Shuaib Khan (Fuel, 2025)

Genetic Divergence Among Sorghum (Sorghum bicolor L.) Genotypes Grown Under Rainfed Conditions - Rafiq Ahmad; Ghulam Shabbir; Syed Farman Ullah; Danish Ibrar; Muhammad Ilyas; Esam M. Al-Shaebi; Yawen Zeng; Abdul Qayyum (Journal of Crop Health, 2025)

Multi-scale computational modeling to identify novel chemical scaffolds as trehalose-6-phosphate phosphatase inhibitors to combat Burkholderia pseudomallei - Sara Noor; Mohammad Abdullah Aljasir; Maryam Bashir; Kalsoom Khan; Sajjad Ahmad; Syed Ainul Abideen; Saifullah Khan; Farhan Siddique; Hamza Ahmad; Khudija Ghani; Madiha Iqbal; Muhammad Irfan; et al. (In Silico Pharmacology, 2025)

Systematic implication of trichome morphology in alpine flora from Hindukush Mountain range - Muhammad Abdullah; Zahid Ullah; Syed Muhammad Iqbal Shah; Mushtaq Ahmad; Amjad Khan; Hussain Shah; Ateef Ullah; Shabir Ahmad; Mohammed Fahad Albeshr; Okezie Emmanuel; Hameed Ullah; Rahman Ali Khan (Genetic Resources and Crop Evolution, 2025)

Fungicide resistance in Fusarium species: exploring environmental impacts and sustainable management strategies - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Muhammad Shahbaz; Aqleem Abbas; Fahad Hakim; Muhammad Shabbir; Yee Shin Tan; Jaya Seelan Sathiya Seelan (Archives of Microbiology, 2025)

Microwave-assisted, sulfhydryl-modified β-cyclodextrin-silymarin inclusion complex: A diverse approach to improve oral drug bioavailability via enhanced mucoadhesion and permeation - Shumaila Arshad; Syed Atif Raza; Alamgeer; Syed Nasir Abbas Bukhari; Nasser F. Alotaibi; Naveed Ahmad; Hafiz Muhammad Irfan; Arshad Mahmood; Mulazim Hussain Asim (Carbohydrate Polymers, 2025)

Spore morphometric analysis in Sino-Himalayan and W-Himalayan Athyriaceae taxa: taxonomic insights and molecular phylogenetic comparison - Syed Nasar Shah; Mushtaq Ahmad; Mohammad Javed Ansari; Muhammad Nauman Khan; Majid Iqbal; Baber Ali; Sami Al Obaid (Genetic Resources and Crop Evolution, 2025)

Taxonomic significance of palyno-morphic markers for the delimitation of some Brassicaceous taxa in Balochistan Province (Pakistan) - Wajia Noor; Muhammad Zafar; Mushtaq Ahmad; Bibi Sadia; Syed Waseem Gillani; Muhammad Manzoor; Maria Ameen (Genetic Resources and Crop Evolution, 2025)

Taxonomic implications of petiole microanatomical traits among Asteraceae tribes from arid–semiarid regions of Baluchistan, Pakistan - Bibi Sadia; Mushtaq Ahmad; Muhammad Zafar; Wajia Noor; Muhammad Manzoor; Syed Waseem Gillani; Shazia Sultana (Genetic Resources and Crop Evolution, 2025)

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

Characterization and Quantification of Outcrops Exposed Along the Karakoram Highway (KKH) and Part of Central Karakoram National Park (CKNP), North Pakistan; Implications for Geoheritage Assessments and Geosite Recognition - Muhammad Yaseen; Jawad Ahmad; Muhammad Naveed Anjum; Abbas Ali Naseem; Syed Tanvir Shah (Geoheritage, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Sequence variants underlying severe combined immunodeficiency and leukocyte adhesion deficiency type 1 in six consanguineous families - Hajra Fayyaz; Atteaya Zaman; Nighat Haider; Rehmana Waris; Muhammad Hussain; Syed Irfan Raza; Wasim Ahmad; Imran Ullah (Immunogenetics, 2024)

Effect of green synthesized silver nanoparticles on growth and physiological responses of pearl millet under salinity stress - Zakir Ullah; Syed Inzimam Ul Haq; Abd Ullah; Muhammad Ahsan Asghar; Mahmoud F. Seleiman; Khansa Saleem; Fanjiang Zeng; Noor Us Sama; Khalid Kamran; Sheraz Ahmad (Environment, Development and Sustainability, 2024)

Spatio-temporal analysis of hydrometeorological variables for terrestrial and groundwater storage assessment - Muhammad Shareef Shazil; Sheharyar Ahmad; Syed Amer Mahmood; Syed Ali Asad Naqvi; Sanju Purohit; Aqil Tariq (Groundwater for Sustainable Development, 2024)

Microsatellite Markers & Mitochondrial D-Loop Based Phylogenetic And Diversity Analysis In Gabrali Cattle - Farhad Ali; Syed Muhammad Suhail; Farhan Anwar Khan; Ijaz Ahmad (Tropical Animal Health and Production, 2024)

Photocatalytic hydrogen peroxide production: Advances, mechanistic insights, and emerging challenges - Shahid Khan; Muhammad Adnan Qaiser; Waqar Ahmad Qureshi; Syed Najeeb-uz-Zaman Haider; Xiaohui Yu; Weikang Wang; Qinqin Liu (Journal of Environmental Chemical Engineering, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

First report of Pythium aphanidermatum causing stem and root rot disease on sesame (Sesamum indicum L.) in Punjab, Pakistan - Nasir Ahmed Rajput; Muhammad Atiq; Abdul Mubeen Lodhi; Rehana Naz Syed; Owais Iqbal; Muhammad Usman Ali; Muhammad Wahab; Hadeed Ahmad (Journal of Plant Pathology, 2024)

Recent advances of MXene@MOF composites for catalytic water splitting and wastewater treatment approaches - Samreen Afzal; Aziz ur Rehman; Tayyaba Najam; Ismail Hossain; Mostafa A.I. Abdelmotaleb; Sundas Riaz; Md Rezaul Karim; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Chemosphere, 2024)

Integration of dual band radio waves and ensemble-based approach for rice moisture content determination and localisation - Noraini Azmi; Latifah Munirah Kamarudin; Ahmad Shakaff Ali Yeon; Ammar Zakaria; Syed Muhammad Mamduh Syed Zakaria; Hiromitsu Nishizaki; Latifah Mohamed; Xiaoyang Mao; Mohd Hafiz Fazalul Rahiman (Journal of Stored Products Research, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Multinomial classification of NLRP3 inhibitory compounds based on large scale machine learning approaches - Muhammad Ishfaq; Syed Zahid Ali Shah; Ijaz Ahmad; Ziaur Rahman (Molecular Diversity, 2024)

Retraction Note: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Dietary nano-Selenium supplementation improves growth performance, nutrient digestibility and hematology in Cirrhinus mrigala fingerlings - Nisar Ahmad; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Muhammad Mahmood (Journal of Trace Elements in Medicine and Biology, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Insights into the alleviation of cadmium toxicity in rice by nano-zinc and Serendipita indica: Modulation of stress-responsive gene expression and antioxidant defense system activation - Muhammad Faheem Adil; Shafaque Sehar; Zhengxin Ma; Khajista Tahira; Syed Muhammad Hassan Askri; Mohamed A. El-Sheikh; Aqeel Ahmad; Fanrui Zhou; Ping Zhao; Imran Haider Shamsi (Environmental Pollution, 2024)

Characterization of the tubby-like proteins (TLPs) gene family in Cucumis sativus L.: insights into the evolution, structure, and expression patterns under salt stress - Ikram Ullah; Muhammad Uzair; Obaid Ur Rehman; Safira Attacha; Kotb A. Attia; Sheraz Ahmad; Muhammad Salman; Hamid Ali; Muhammad Abdul Rehman Rashid; Asmaa M. Abushady; Sajid Fiaz; Syed Jehangir Shah; et al. (Genetic Resources and Crop Evolution, 2024)

Binary mixture of ionic liquid and span 80 for oil spill remediation: Synthesis and performance evaluation - Masooma Nazar; Aqeel Ahmad; Syed Muhammad Shakil Hussain; Muhammad Moniruzzaman (Marine Pollution Bulletin, 2024)

Association of polymorphism in the promotor area of the caprine BMPR1B gene with litter size and body measurement traits in Damani goats - Inayat Ullah; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Farhan Anwar Khan; Muhammad Shoaib; Kamran Farid; Amel Ayari-Akkari; Ekhlas Ali Morfeine (Tropical Animal Health and Production, 2024)

Assessing the impact of geopolitical, economic, and institutional factors on China's environmental management in the Russian-Ukraine conflicting era - Bilal Ahmed; Salman Wahab; Syed Rahim; Muhammad Imran; Afaq Ahmad Khan; Mohammed Moosa Ageli (Journal of Environmental Management, 2024)

Aspects of superior photocatalytic dye degradation and adsorption efficiency of reduced graphene oxide multiwalled carbon nanotubes with modified ZnO-Al2O3 nanocomposites - Ajaz Ahmad Wani; Ryhan Abdullah Rather; Norazuwana Shaari; Umair Khan; Taseer Muhammad; Syed Modassir Hussain; Laila F. Seddek; Ahmed M. Abed (Journal of Environmental Chemical Engineering, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Retraction Note: The non-linear relationship between carbon dioxide emissions, financial development and energy consumption in developing European and Central Asian economies - Leng Chunyu; Syed Zain-ul-Abidin; Wajeeha Majeed; Syed Muhammad Faraz Raza; Ishtiaq Ahmad (Environmental Science and Pollution Research, 2024)

Seasonal Variation and Association of Heavy Metals in the Vital Organs of Edible Fishes from the River Jhelum in Punjab, Pakistan - Iram Inayat; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Khawaja Raees Ahmad; Muhammad Ali Kanwal; Rabiyah Ali; Rameen Khalid; Syed Sikandar Habib (Biological Trace Element Research, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

A comparison of experimental and computational methods for circular footing response on lime-treated geotextile reinforced silty sand - Syed Md Yousuf; Mehboob Anwar Khan; Syed Muhammad Ibrahim; Anil Kumar Sharma; Furquan Ahmad; Pramod Kumar (Modeling Earth Systems and Environment, 2024)

Integration of chitosan coating and short-term hypobaric treatment extends postharvest life and upregulates defense-related enzymes in apple fruit - Syed Umair Shah; Majid S. Hashmi; Muhammad Rafiullah Khan; Ayaz Ahmad; Aysha Riaz; Yosef Al Shoffe; Said Wahab; Muhammad Ayub; Antonio Ippolito (European Journal of Plant Pathology, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Enabling marine conservation through education: Insights from the Malaysian Nature Society - E.I. Ahmad-Kamil; Sharifah Zarina Syed Zakaria; Murnira Othman; Foong Ling Chen; Muhammad Yazid Deraman (Journal of Cleaner Production, 2024)

Advancements in Ni and Co-based catalysts for sustainable syngas production via Bi-reforming of methane: A review of recent advances - Syed Muhammad Wajahat ul Hasnain; Ahmad Salam Farooqi; Bamidele Victor Ayodele; Abid Salam Farooqi; Khairuddin Sanaullah; Bawadi Abdullah (Journal of Cleaner Production, 2024)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Exploring the hidden treasures of Nitella hyalina: a comprehensive study on its biological compounds, nutritional profile, and unveiling its antimicrobial, antioxidative, and hypoglycemic properties - Muhammad Imran; Arshad Iqbal; Syed Lal Badshah; Imtiaz Ahmad; Ashwag Shami; Baber Ali; Fatema Suliman Alatawi; Mohsen Suliman Alatawi; Yasser S. Mostafa; Saad A. Alamri; Ahlam A. Alalwiat; Majed A. Bajaber (World Journal of Microbiology and Biotechnology, 2023)

Polymorphism and association study of lactoferrin (LF) gene with milk yield, milk composition, and somatic cell count in Beetal goats - Lionel Kinkpe; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Farhan Anwar Khan; Amel Ayari-Akkari; Sazada Siddiqui (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Production, purification, and characterization of p-diphenol oxidase (PDO) enzyme from lignolytic fungal isolate Schizophyllum commune MF-O5 - Muhammad Faheem; Syed Ali Imran Bokhari; Muhammad Arshad Malik; Bashir Ahmad; Muhammad Riaz; Nafeesa Zahid; Adil Hussain; Abdul Ghani; Hanif Ullah; Waseem Shah; Rashid Mehmood; Khurshid Ahmad; et al. (Folia Microbiologica, 2023)

Molecular characterization of lumpy skin disease virus from recent outbreaks in Pakistan - Shumaila Manzoor; Muhammad Abubakar; Aziz Ul-Rahman; Zainab Syed; Khurshid Ahmad; Muhammad Afzal (Archives of Virology, 2023)

Genomic and biotechnological potential of a novel oil-degrading strain Enterobacter kobei DH7 isolated from petroleum-contaminated soil - Muhammad Zohaib Nawaz; Chunyan Xu; Majjid A. Qaria; Syed Zeeshan Haider; Hafiz Rameez Khalid; Huda Ahmed Alghamdi; Iqrar Ahmad Khan; Daochen Zhu (Chemosphere, 2023)

Development of high resolution daily gridded precipitation and temperature dataset for potohar plateau of indus basin - Muhammad Wasif Khan; Shakil Ahmad; Zakir Hussain Dahri; Zain Syed; Khalil Ahmad; Firdos Khan; Muhammad Azmat (Theoretical and Applied Climatology, 2023)

Utilization of cereal-based husks to achieve sustainable development goals: Treatment of wastewater, biofuels, and biodegradable packaging - Syed Ali Hassan; Mueen Abbas; Waqar Mujahid; Waqar Ahmed; Saeed Ahmad; Abid Aslam Maan; Aamir Shehzad; Zuhaib F. Bhat; Rana Muhammad Aadil (Trends in Food Science & Technology, 2023)

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Estimating Photosynthetically Active Euphotic Layer in Major Lakes of Kumaun Region Using Secchi Depth - Zainab Khan; Sk Ajim Ali; Mohammad Mohsin; Syed Kausar Shamim; Ekaterina Mankovskaya; Farhana Parvin; Nikhat Bano; Ateeque Ahmad; Muhammad Yousuf Jat Baloch (Water, Air, & Soil Pollution, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Colloidal gold based immunochromatographic detection of Mycoplasmopsis synoviae infection and its prevalence in avian species of Karachi, Pakistan - Nida Rehman; Uroosa Ejaz; Amal Siraj; Shazma Liaquat; Muhammad Sohail; Taseer Ahmed Khan; Syed Faraz Moin; Aqeel Ahmad (Research in Veterinary Science, 2023)

Diversity in Elemental Content in Selected Artemisia L. (Asteraceae) Species from Gilgit-Baltistan Region of Pakistan Based on Inductively Coupled Plasma Atomic Emission Spectrophotometry (ICP-AES) - Adil Hussain; Muhammad Sajid; Daniel Potter; Hassam Rasheed; Mujtaba Hassan; Naeem Akhtar; Bashir Ahmad; Syed Ali Imran Bokhari (Biological Trace Element Research, 2023)

Exploring the asymmetric effects of urbanization and trade on CO2 emissions: fresh evidence from Pakistan - Xiongfeng Pan; Aneela Ashraf; Syed Muhammad Faraz Raza; Fazliddin Nasriddinov; Maaz Ahmad (Environmental Science and Pollution Research, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

The efficiency of boric acid as an alternate to NaCl for the preservation of cattle hides - Umaid Shifa; Rajwali Khan; Syed Muhammad Suhail; Ijaz Ahmad; Abdur Rahman; Amel Ayari Akkari; Habab M. Yassin (Tropical Animal Health and Production, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Effect of dietary inclusion of mealworm frass on growth, hematology, and serum biochemistry of sheep - Muhammad Ayaz; Rajwali Khan; Sarzamin Khan; Syed Muhammad Suhail; Khalid Khan; Ijaz Ahmad; Abdul Wahab; Amel Ayari-Akkari; Gehan Othman (Tropical Animal Health and Production, 2023)

Preliminary Geoheritage Assessment of The Gharam Chashma Granitic Batholith (GCGB), Southern Margin of Asian Plate, NW Pakistan: Multiple Constraints from Field Evidence, Petrology, and Physicomechanical Properties - Abbas Ali Naseem; Muhammad Naveed Anjum; Muhammad Yaseen; Muhammad Ali; Waqar Inam; Syed Haroon Ali; Jawad Ahmad; Anees Ahmad Bangash (Geoheritage, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

The impact of brick kilns on environment and society: a bibliometric and thematic review - Muhammad Arham Parvez; Irfan Ahmad Rana; Adnan Nawaz; Hafiz Syed Hamid Arshad (Environmental Science and Pollution Research, 2023)

Nanoparticles assisted regulation of oxidative stress and antioxidant enzyme system in plants under salt stress: A review - Muhammad Zia-ur-Rehman; Sidra Anayatullah; Effa Irfan; Syed Makhdoom Hussain; Muhammad Rizwan; Muhammad Irfan Sohail; Muhammad Jafir; Tanveer Ahmad; Muhammad Usman; Hesham F. Alharby (Chemosphere, 2023)

Occurrence and Distribution of Heavy Metals in Mining Degraded Soil and Medicinal Plants: A Case Study of Pb/Zn Sulfide Terrain Northern Areas, Pakistan - Javed Nawab; Muhammad Idress; Sajid Ullah; Gul Rukh; Rimsha Zainab; Hassan Sher; Junaid Ghani; Sardar Khan; Zahid Ullah; Imran Ahmad; Syed Weqas Ali (Bulletin of Environmental Contamination and Toxicology, 2023)

Invasive success of Ipomoea carnea Jacq. through plasticity in physio-anatomical and phytochemical traits across diversified habitats - Syed Mohsan Raza Shah; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Muhammad Ashfaq Wahid (Biological Invasions, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Correction to: Effect of eco‑friendly probiotics‑supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Effect of eco-friendly probiotics-supplemented rapeseed meal–based diet on the performance of Catla catla fingerlings - Muhammad Mudassar Shahzad; Syed Makhdoom Hussain; Majid Hussain; Naveed Ahmad; Laraib Tahir; Kalsoom Akhtar (Environmental Science and Pollution Research, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Reverse vaccinology approach for multi-epitope centered vaccine design against delta variant of the SARS-CoV-2 - Khurshid Jalal; Kanwal Khan; Zarrin Basharat; Muhammad Naseer Abbas; Reaz Uddin; Fawad Ali; Saeed Ahmad Khan; Syed Shams ul Hassan (Environmental Science and Pollution Research, 2022)

Change in forest biomass with altitudinal variations in dry temperate forest of Dir Kohistan, Pakistan - Syed Tufail Ahmad; Ahmad Hussain; Saif Ullah; Aitezaz Muhammad Khan; Muhammad Sadiq Khan; Inam Ullah (Modeling Earth Systems and Environment, 2022)

Recent trends in microalgal harvesting: an overview - Natasha Laraib; Ali Hussain; Arshad Javid; Tahir Noor; Qurat-ul-Ain Ahmad; Asma Chaudhary; Maleeha Manzoor; Muhammad Akmal; Syed Mohsin Bukhari; Waqas Ali; Tae Jin Choi; Peer M. Schenk (Environment, Development and Sustainability, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Synthesis of 1,2,3-benzotriazin-4(3H)-one derivatives as α-glucosidase inhibitor and their in-silico study - Zunera Khalid; Syed S. Shafqat; Hafiz A. Ahmad; Hafiz M. Rehman; Munawar A. Munawar; Matloob Ahmad; Abdullah M. Asiri; Muhammad Ashraf (Medicinal Chemistry Research, 2022)

Strategic combination of metal–organic frameworks and C3N4 for expeditious photocatalytic degradation of dye pollutants - Ome Parkash Kumar; Muhammad Ahmad; Muhammad Altaf Nazir; Aqsa Anum; Muhammad Jamshaid; Syed Shoaib Ahmad Shah; Aziz Rehman (Environmental Science and Pollution Research, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

Triggering sustainable firm performance, supply chain competitive advantage, and green innovation through lean, green, and agile supply chain practices - Muhammad Waqas; Xue Honggang; Naveed Ahmad; Syed Abdul Rehman Khan; Zia Ullah; Muzaffar Iqbal (Environmental Science and Pollution Research, 2022)

Knowledge, attitude, and practice of clinicians about antimicrobial stewardship and resistance among hospitals of Pakistan: a multicenter cross-sectional study - Sohaib Ashraf; Shoaib Ashraf; Moneeb Ashraf; Muhammad Ahmad Imran; Zawar Ahmad Choudhary; Hadiqa Tul Hafsa; Abeer Bin Awais; Larab Kalsoom; Iqra Farooq; Zaighum Habib; Sidra Ashraf; Qurrat Ul Ain Iqbal; et al. (Environmental Science and Pollution Research, 2022)

A novel protein truncating mutation in L2HGDH causes L-2-hydroxyglutaric aciduria in a consanguineous Pakistani family - Muhammad Muzammal; Muhammad Zeeshan Ali; Beatrice Brugger; Jasmin Blatterer; Safeer Ahmad; Sundas Taj; Syed Khizar Shah; Saadullah Khan; Christian Enzinger; Erwin Petek; Klaus Wagner; Muzammil Ahmad Khan; et al. (Metabolic Brain Disease, 2022)
Background L-2-hydroxyglutaric aciduria (L2HGA) is a rare neurometabolic disorder that occurs due to accumulation of L-2-hydroxyglutaric acid in the cerebrospinal fluid (CSF), plasma and urine. The clinical manifestation of L2HGA includes intellectual disability, cerebellar ataxia, epilepsy, speech problems and macrocephaly. Methods In the present study, we ascertained a multigenerational consanguineous Pakistani family with 5 affected individuals. Clinical studies were performed through biochemical tests and brain CT scan. Locus mapping was carried out through genome-wide SNP genotyping, whole exome sequencing and Sanger sequencing. For in silico studies protein structural modeling and docking was done using I-TASSER, Cluspro and AutoDock VINA tools. Results Affected individuals presented with cognitive impairment, gait disturbance, speech difficulties and psychomotor delay. Radiologic analysis of a male patient revealed leukoaraiosis with hypoattenuation of cerebral white matter, suggestive of hypomyelination. Homozygosity mapping in this family revealed a linkage region on chromosome 14 between markers rs2039791 and rs781354. Subsequent whole exome analysis identified a novel frameshift mutation NM_024884.3:c.180delG, p.(Ala62Profs*24) in the second exon of L2HGDH . Sanger sequencing confirmed segregation of this mutation with the disease phenotype. The identification of the most N-terminal loss of function mutation published thus far further expands the mutational spectrum of L2HGDH.

Synthesis and evaluation of Ca-doped ferrihydrite as a novel adsorbent for the efficient removal of fluoride - Khalil Ahmad; Izaz Ali Shah; Sharafat Ali; Muhammad Tariq Khan; Muhammad Bilal Ahmed Qureshi; Syed Hassan Ali Shah; Asmat Ali; Wajid Rashid; Hifza Nayab Gul (Environmental Science and Pollution Research, 2022)

An analysis on the effect of coronavirus (COVID-19) pandemic movement control order (MCOS) on the solid waste generation in Peninsular Malaysia - Muhammad Afiq Brohan; Nazri Che Dom; Ahmad Razali Ishak; Samsuri Abdullah; Hasber Salim; Sharifah Norkhadijah Syed Ismail; Nopadol Precha (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: The non-linear relationship between carbon dioxide emissions, financial development and energy consumption in developing European and Central Asian economies - Leng Chunyu; Syed Zain-ul-Abidin; Wajeeha Majeed; Syed Muhammad Faraz Raza; Ishtiaq Ahmad (Environmental Science and Pollution Research, 2021)

Heavy Metals Accumulation in Dragonflies (Odonata) and Their Habitats in District Swabi, Khyber Pakhtunkhwa, Pakistan: Assessing Dragonfly Bionomics in the Region - Hajra Noor-Ul-Islam; Khurshaid Khan; Syed Ahmed Zia; Muhammad Naeem; Waqas Ahmad Shams (Bulletin of Environmental Contamination and Toxicology, 2021)

Mitochondrial phylogenetic and diversity analysis in Azi-Kheli buffalo - Farhad Ali; Ijaz Ahmad; Muhammad Ijaz Ali; Muhammad Hasnain Riaz; Nadar Khan; Obaid Ullah; Faizul Hassan; Syed Muhammad Suhail; Rajwali Khan; Muhammad Tahir Khan; Irshad Ahmad; Muhammad Tariq Zeb (Tropical Animal Health and Production, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Inhibition of jack bean urease by amphiphilic peptides - Zafar Ali Shah; Sadam Hussain; Serab Khan; Nawab Ali; Samiullah Burki; Syed Uzair Ali Shah; Ashfaq Ahmad; Faiz -Ur-Rehman; Muhammad Nasimullah Qureshi; Syed Muhammad Mukrram Shah; Farzana Shaheen (Medicinal Chemistry Research, 2021)

Livelihood diversification in managing catastrophic risks: evidence from flood-disaster regions of Khyber Pakhtunkhwa Province of Pakistan - Ashfaq Ahmad Shah; Zaiwu Gong; Nasir Abbas Khan; Imran Khan; Muhammad Ali; Syed Asif Ali Naqvi (Environmental Science and Pollution Research, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Nonclinical Features in Predictive Modeling of Cardiovascular Diseases: A Machine Learning Approach - Mirza Rizwan Sajid; Noryanti Muhammad; Roslinazairimah Zakaria; Ahmad Shahbaz; Syed Ahmad Chan Bukhari; Seifedine Kadry; A. Suresh (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Molecular docking of alpha-enolase to elucidate the promising candidates against Streptococcus pneumoniae infection - Muhammad Hassan; Atif Amin Baig; Syed Awais Attique; Shafqat Abbas; Fizza Khan; Sara Zahid; Qurat Ul Ain; Muhammad Usman; Nordin Bin Simbak; Mohammad Amjad Kamal; Hanani Ahmad Yusof (DARU Journal of Pharmaceutical Sciences, 2021)

RETRACTED ARTICLE: The step towards environmental mitigation in Pakistan: do transportation services, urbanization, and financial development matter? - Danish Iqbal Godil; Paiman Ahmad; Muhammad Sajjad Ashraf; Salman Sarwat; Arshian Sharif; Syed Shabib-ul-Hasan; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Alkaline lipase production by novel meso-tolerant psychrophilic Exiguobacterium sp. strain (AMBL-20) isolated from glacier of northeastern Pakistan - Muhammad Talha Yasin; Yasir Ali; Khurshid Ahmad; Abdul Ghani; Kinza Amanat; Muhammad Mudassir Basheir; Muhammad Faheem; Saddam Hussain; Bashir Ahmad; Adil Hussain; Syed Ali Imran Bokhari (Archives of Microbiology, 2021)

Survival Strategies in Khavi Grass [Cymbopogon jwarancusa (Jones) Schult.] Colonizing Hot Hypersaline and Arid Environments - Sana Fatima; Mansoor Hameed; Nargis Naz; Syed Mohsan Raza Shah; Mehwish Naseer; Muhammad Sajid Aqeel Ahmad; Muheammad Ashraf; Farooq Ahmad; Sangam Khalil; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2021)

Synthetic β-hydroxy ketone derivative inhibits cholinesterases, rescues oxidative stress and ameliorates cognitive deficits in 5XFAD mice model of AD - Syed Ilyas Ahmad; Gowhar Ali; Tahir Muhammad; Rahim Ullah; Muhammad Naveed Umar; Aisha Nasir Hashmi (Molecular Biology Reports, 2020)

Measuring education sector resilience in the face of flood disasters in Pakistan: an index-based approach - Ashfaq Ahmad Shah; Zaiwu Gong; Muhammad Ali; Ali Jamshed; Syed Asif Ali Naqvi; Shaista Naz (Environmental Science and Pollution Research, 2020)

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

Determination of oil contents from eight varieties of olea europaea (Olive) grown in Pakistan - Abdul Khaliq; Syed Muhammad Ali Shah; Muhammad Akram; Naveed Munir; Muhammad Daniyal; Muhammad Irshad; Saeed Ahmad (Natural Product Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Fabrication and Characterization of Thiolated Chitosan Microneedle Patch for Transdermal Delivery of Tacrolimus - Zulcaif Ahmad; Muhammad Imran Khan; Muhammad Irfan Siddique; Hafiz Shoaib Sarwar; Gul Shahnaz; Syed Zajif Hussain; Nadeem Irfan Bukhari; Irshad Hussain; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Genotyping of methicillin-resistant Staphylococcus aureus from sepsis patients in Pakistan and detection of antibodies against staphylococcal virulence factors - Stefan Monecke; Muhammad Ali Syed; Mushtaq Ahmad Khan; Shehzad Ahmed; Sadia Tabassum; Darius Gawlik; Elke Müller; Annett Reissig; Sascha D. Braun; Ralf Ehricht (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Probing the effect of various lipids and polymer blends on clopidogrel encapsulated floating microcarriers - Saba Irshad; Ikram Ullah Khan; Syed Haroon Khalid; Sajid Asghar; Muhammad Irfan; Ikrima Khalid; Nadeem Sabir; Adnan Ali; Ahmad Nawaz Khan; Abid Mehmood Yousaf; Talib Hussain; Yasser Shahzad (DARU Journal of Pharmaceutical Sciences, 2019)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Zinc-lysine prevents chromium-induced morphological, photosynthetic, and oxidative alterations in spinach irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Rizwan; Firdaus-e- Bareen; Zohaib Abbas; Syed Asad Hussain Bukhari; Leonard Wijaya; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Estimation of Canal Water Deficit Using Satellite Remote Sensing and GIS: A Case Study in Lower Chenab Canal System - Muhammad Mohsin Waqas; Usman Khalid Awan; Muhammad Jehanzeb Masud Cheema; Ishfaq Ahmad; Matlob Ahmad; Sikandar Ali; Syed Hamid Hussain Shah; Allah Bakhsh; Muhammad Iqbal (Journal of the Indian Society of Remote Sensing, 2019)

Taxonomic significance of leaf epidermis in tribe Trifolieae L. (Leguminosae; Papilionoideae) in Pakistan - Neelam Rashid; Muhammad Zafar; Mushtaq Ahmad; Mir Ajab Khan; Khafsa Malik; Shazia Sultana; Syed Nasar Shah (Plant Biosystems, 2019)

Detection of mineral alteration induced by hydrocarbon microseepages by using remotely sensed data in the Fateh Jang area of the Northern Potwar region of Pakistan - Ayesha Habib; Muhammad Khubaib Abuzar; Ijaz Ahmad; Urooj Shakir; Syed Amer Mahmood; Mumtaz Ali Khan; Muhammad Fahad Mahmood (Arabian Journal of Geosciences, 2019)

Optimizing irrigation and nitrogen requirements for maize through empirical modeling in semi-arid environment - Ishfaq Ahmad; Syed Aftab Wajid; Ashfaq Ahmad; Muhammad Jehanzeb Masud Cheema; Jasmeet Judge (Environmental Science and Pollution Research, 2019)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Silicon-mediated growth and yield improvement of sunflower (Helianthus annus L.) subjected to brackish water stress - Syed Azhar Hussain; Muhammad Ansar Farooq; Javaid Akhtar; Zulfiqar Ahmad Saqib (Acta Physiologiae Plantarum, 2018)

Preparation and Evaluation of Skin Wound Healing Chitosan-Based Hydrogel Membranes - Sarfaraz Ahmad; Muhammad Usman Minhas; Mahmood Ahmad; Muhammad Sohail; Orva Abdullah; Syed Faisal Badshah (AAPS PharmSciTech, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Flood hazards: household vulnerability and resilience in disaster-prone districts of Khyber Pakhtunkhwa province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Jahangir Khan; Syed Muhammad Amir (Natural Hazards, 2018)

Hospital-acquired methicillin-resistant Staphylococcus aureus (MRSA) from Pakistan: molecular characterisation by microarray technology - Bushra Jamil; Darius Gawlik; Muhammad Ali Syed; Asim Ali Shah; Shahid Ahmad Abbasi; Elke Müller; Annett Reißig; Ralf Ehricht; Stefan Monecke (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Recent trends in ring opening of epoxides with sulfur nucleophiles - Sajjad Ahmad; Ameer Fawad Zahoor; Syed Ali Raza Naqvi; Muhammad Akash (Molecular Diversity, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Satellite-based rainfall estimation and discharge measurement of Middle Indus River, Pakistan - Syed Muhammad Zubair Younis; Muhammad Majid; Ahmad Ammar (Arabian Journal of Geosciences, 2017)

Effect of Rheology and Poloxamers Properties on Release of Drugs from Silicon Dioxide Gel-Filled Hard Gelatin Capsules—A Further Enhancement of Viability of Liquid Semisolid Matrix Technology - Misbah Sultana; Mobashar Ahmad Butt; Tariq Saeed; Rizwan Mahmood; Saeed ul Hassan; Khalid Hussain; Syed Atif Raza; Muhammad Ahsan; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Synthesis, in vitro potential and computational studies on 2-amino-1, 4-dihydropyrimidines as multitarget antibacterial ligands - Muhammad Jawad Ahmad; Syed Fahad Hassan; Riffat Un Nisa; Khurshid Ayub; Muhammad Shahid Nadeem; Samina Nazir; Farzana Latif Ansari; Naveeda Akhtar Qureshi; Umer Rashid (Medicinal Chemistry Research, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Potato Starch as a Coagulant for Dye Removal from Textile Wastewater - Muhammad Shahzad Zafar; Muhammad Tausif; Muhammad Mohsin; Syed Waqas Ahmad; Muhammad Zia-ul-Haq (Water, Air, & Soil Pollution, 2015)

Evaluating pasture and soil allowance of manganese for Kajli rams grazing in semi-arid environment - Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Ashraf; Syed Ali Hassan Naqvi; Alireza Seidavi; Nudrat Aisha Akram; Vito Laudadio; Vincenzo Tufarelli (Tropical Animal Health and Production, 2015)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

Photodegradation of Moxifloxacin in Aqueous and Organic Solvents: A Kinetic Study - Iqbal Ahmad; Raheela Bano; Syed Ghulam Musharraf; Sofia Ahmed; Muhammad Ali Sheraz; Qamar ul Arfeen; Muhammad Salman Bhatti; Zufi Shad (AAPS PharmSciTech, 2014)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

A novel WDR62 mutation causes primary microcephaly in a Pakistani family - Mazhar Mustafa Memon; Syed Irfan Raza; Sulman Basit; Rizwana Kousar; Wasim Ahmad; Muhammad Ansar (Molecular Biology Reports, 2013)

Molecular simulations of bergenin as a new urease inhibitor - Mohammad Arfan; Hazrat Amin; Inamullah Khan; Muhammad Raza Shah; Hamidullah Shah; Amir Zada Khan; Syed Muhammad Ashhad Halimi; Nematullah Khan; Waqar Ahmad Kaleem; Mughal Qayum; Adnan Shahidullah; Muhammad Azam Khan (Medicinal Chemistry Research, 2012)

Novel quinolyl-thienyl chalcones and their 2-pyrazoline derivatives with diverse substitution pattern as antileishmanial agents against Leishmania major - Syed Umar Farooq Rizvi; Hamid Latif Siddiqui; Muhammad Nisar Ahmad; Matloob Ahmad; Mujahid Hussain Bukhari (Medicinal Chemistry Research, 2012)

Beta Glucan: A Valuable Functional Ingredient in Foods - Asif Ahmad; Faqir Muhammad Anjum; Tahir Zahoor; Haq Nawaz; Syed Muhammad Raihan Dilshad (Critical Reviews in Food Science and Nutrition, 2012)

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes - Umm-e-Kalsoom; Sulman Basit; Syed Kamran-ul-Hassan Naqvi; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2012)

Co-Ion Effect on Cr3+ Sorption by Amberlyst-15(H+) - Syed Mustafa; Khizar Hussain Shah; Abdul Naeem; Muhammad Waseem; Tauqeer Ahmad; Sadullah Khan (Water, Air, & Soil Pollution, 2011)

Using leaf tip necrosis as a phenotypic marker to predict the presence of durable rust resistance gene pair Lr34/Yr18 in wheat - Syed Jawad Ahmad Shah; Shaukat Hussain; Musharaf Ahmad; Farhatullah; Iftikhar Ali; Muhammad Ibrahim (Journal of General Plant Pathology, 2011)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

Transfer of radioactivity from soil to vegetation in Rechna Doab, Pakistan - Abdul Jabbar; Muhammad Tufail; Waheed Arshed; Arshed Salem Bhatti; Syed Salman Ahmad; Perveen Akhter; Muhammad Dilband (Isotopes in Environmental and Health Studies, 2010)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Kinetics of Chromium Ion Removal from Tannery Wastes Using Amberlite IRA-400 Cl− and its Hybrids - Syed Mustafa; Tauqeer Ahmad; Abdul Naeem; Khizar Hussain Shah; Muhammad Waseem (Water, Air, & Soil Pollution, 2010)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

A syndromic form of autosomal recessive congenital microcephaly (Jawad syndrome) maps to chromosome 18p11.22–q11.2 - Muhammad Jawad Hassan; Muhammad Salman Chishti; Syed Muhammad Jamal; Muhammad Tariq; Wasim Ahmad (Human Genetics, 2008)

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis - Ghazanfar Ali; Muhammad Salman Chishti; Syed Irfan Raza; Peter John; Wasim Ahmad (Human Genetics, 2007)

Defective glycosylation of decorin and biglycan, altered collagen structure, and abnormal phenotype of the skin fibroblasts of an Ehlers–Danlos syndrome patient carrying the novel Arg270Cys substitution in galactosyltransferase I (β4GalT-7) - Daniela G. Seidler; Muhammad Faiyaz-Ul-Haque; Uwe Hansen; George W. Yip; Syed H. E. Zaidi; Ahmad S. Teebi; Ludwig Kiesel; Martin Götte (Journal of Molecular Medicine, 2006)

Localization of a novel locus for alopecia with mental retardation syndrome to chromosome 3q26.33–q27.3 - Peter John; Ghazanfar Ali; Muhammad S. Chishti; Syed Muhammad S. Naqvi; Suzanne M. Leal; Wasim Ahmad (Human Genetics, 2006)

Morpho-anatomical responses ofTrigonella foenum graecum Linn. to induced cadmium and lead stress - Syed Hilal Ahmad; Zafar Reshi; Javed Ahmad; Muhammad Iqbal (Journal of Plant Biology, 2005)